Grete Kellenberger-Gujer: Molecular biology research pioneer. Issue 2 (2nd April 2016) - Citi, Sandra; Berg, Douglas E.
ABSTRACT: Grete Kellenberger-Gujer was a Swiss molecular biologist who pioneered fundamental studies of bacteriophage in the mid-20 th century at the University of Geneva. Her life and career stories are reviewed here, focusing on her fundamental contributions to our early understanding of phage biology via her insightful analyses of phenomena such as the lysogenic state of a temperate phage (λ), genetic recombination, radiation's in vivo consequences, and DNA restriction-modification; on her creative personality and interactions with peers; and how her academic advancement was affected by gender, societal conditions and cultural attitudes of the time. Her story is important scientifically, putting into perspective features of the scientific community from just before the molecular biology era started through its early years, and also sociologically, in illustrating the numerous "glass ceilings" that, especially then, often hampered the advancement of creative women.